Efficient syntheses of zoledronic acid as an active ingredient of a drug against osteoporosis. Issue 6 (19th March 2018) - Nagy, Dávid Illés; Grün, Alajos; Lévay, Krisztina; Garadnay, Sándor; Greiner, István; Keglevich, György
ABSTRACT: The reaction of 1 H -imidazol-1-ylacetic acid and two equivalents of phosphorus trichloride/phosphorous acid at 75 °C in sulfolane, or in the presence of catalytic amounts of [bmim][BF4 ] afforded zoledronic acid in yields up to 75%. The joint use of the ionic liquid additive and sulfolane as the solvent was synergetic affording highly valuable zoledronic acid in a record yield of 93%. GRAPHICAL ABSTRACT: